The Effect of Lymph Node Harvest on Prognosis in Locally Advanced Middle-Low Rectal Cancer After Neoadjuvant Chemoradiotherapy - Lin, Zhuangbin; Li, Xiaobo; Song, Jianyuan; Zheng, Rong; Chen, Cheng; Li, Anchuan; Xu, Benhua (Frontiers in Oncology, 2022)
Objective: The purpose of this study was to investigate the relationship between lymph node harvest and the prognosis in locally advanced rectal cancer (LARC) patients after neoadjuvant chemoradiotherapy (nCRT). Methods: Patients who were diagnosed with clinical LARC and treated with nCRT and radical surgery between June 2008 and July 2017 were included in this study. The relationship between lymph node retrieval and prognosis was analyzed. Other lymph node-related indicators were explored. Results: A total of 837 patients with a median follow-up of 61 (7-139) months were included in the study. The five-year DFS and OS rates of all patients were 74.9% and 82.3%, respectively. Multivariate survival analysis suggested that dissection of ≥ 12 lymph nodes did not improve OS or DFS. 7 was selected as the best cutoff value for the total number of lymph nodes retrieved by Cox multivariate analysis (χ2=10.072, HR: 0.503, P=0.002). Dissection of ≥ 5 positive lymph nodes (PLNs) was an independent prognostic factor for poorer DFS (HR: 2.104, P=0.004) and OS (HR: 3.471, p<0.001). A positive lymph node ratio (LNR) of more than 0.29 was also an independent prognostic factor for poorer DFS (HR: 1.951, P=0.002) and OS (HR: 2.434, p<0.001). Conclusion: The recommends that at least 7 harvested lymph nodes may be more appropriate for LARC patients with nCRT. PLN and LNR may be prognostic factors for LARC patients with ypN+ after nCRT.